Heat capacities and thermal diffusivities of some n-alkanoic acid methyl esters. (January 2019) - Bogatishcheva, Nataliya S.; Faizullin, Mars Z.; Nikitin, Eugene D.
Highlights: Heat capacities and thermal diffusivities of seven n-alkanoic acid methyl esters were measured. The esters studied have 6–12 carbon atoms in a parent acid. The esters investigated are the components of biodiesel. Abstract: The heat capacities and thermal diffusivities of n-alkanoic acid methyl esters Cn H2n−1 O2 CH3 with n from 6 to 12 have been measured. The heat capacities have been measured in the temperature range from 303.15 K to 373.15 K; the measurements of thermal diffusivity have been carried out for a given methyl ester from 303.15 K to the temperature at which a noticeable evaporation of the ester took place. The temperature dependencies of the heat capacities and thermal diffusivities have been approximated by a third-order and a first-order polynomial, respectively. It has been shown that the dependence of the molar heat capacity on n ( n = 1–14) at a temperature of 298.15 K is close to linear.